2011
DOI: 10.1080/03235400903024878
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity ofPiper guineenseSchum. & Thonn seed andMoringa oleiferaLam. leaf powder againstTrogoderma granariumEverts (Coleoptera: Dermestidae)

Abstract: Laboratory studies were carried out to investigate bioactivity of Piper guineense seeds and Moringa oleifera leaf powders applied singly or in a mixture against larvae and adult Trogoderma granarium Everts in airtight containers. Three levels (0.0 g, 0.5 g, and 1.0 g/20 g groundnut seeds) of the plant powders were used and pirimiphos-methyl was applied at 0.01 g/20 g seeds (recommended dose). Another control consisting of untreated seeds with aerated lids was included in the bioassay. Both larvae and adults we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…This finding agrees with that of Ogendo et al (2004) who reported more than 50% induced mortality by Tephrosia vogelii extracts on Sitophilus zeamais. Similar finding was also reported by Babarinde et al (2001) that leaf and seeds powders of Piper guineense and Moringa oleifera were effective showed effective bioactivity against Trogoderma granarium. Adebayo ( 2003) also reported insecticidal activity of botanical insecticides in the control of insect pests of okra and cowpea.…”
Section: Discussionsupporting
confidence: 90%
“…This finding agrees with that of Ogendo et al (2004) who reported more than 50% induced mortality by Tephrosia vogelii extracts on Sitophilus zeamais. Similar finding was also reported by Babarinde et al (2001) that leaf and seeds powders of Piper guineense and Moringa oleifera were effective showed effective bioactivity against Trogoderma granarium. Adebayo ( 2003) also reported insecticidal activity of botanical insecticides in the control of insect pests of okra and cowpea.…”
Section: Discussionsupporting
confidence: 90%
“…It is a good source of nectar used by the honey bees for production of honey (Babarinde, 2009). Its insecticidal potentials against many insect pests have been reported by several authors (Babarinde et al, 2011;Ashfaq and Ashfaq, 2012;Santos et al, 2018). Cashew nut shell liquid (CNSL) contains a high proportion of phenolic compound, Anarcadic acid and Cardole (Oparaeke et al, 2005;Olotuah and Ofuya, 2010;Mukhopadyay et al,2010).…”
Section: Introductionmentioning
confidence: 73%
“…Extracts of spice and other medicinal higher plants have been reported to exhibit appreciable levels of insect killing activities (Amuji et al, 2012). Many workers have reported that extracts of T. vogelii exhibited strong insecticidal activity against several insect pests of agricultural crops (Adebayo 2003;Babarinde et al, 2001). According to Koona and Dorn (2005), powdered hexane extracts of dried leaves of T. vogelii effectively protected legumes seeds in storage against attacks from bruchids and reduced the damage caused by Callosobrunchus maculatus.…”
Section: Discussionmentioning
confidence: 99%